2014
DOI: 10.3758/s13428-014-0524-5
|View full text |Cite
|
Sign up to set email alerts
|

Response latencies are alive and well for identifying fakers on a self-report personality inventory: A reconsideration of van Hooft and Born (2012)

Abstract: Van Hooft and Born (Journal of Applied Psychology 97: [301][302][303][304][305][306][307][308][309][310][311][312][313][314][315][316] 2012) presented data challenging both the correctness of a congruence model of faking on personality test items and the relative merit (i.e., effect size) of response latencies for identifying fakers. We suggest that their analysis of response times was suboptimal, and that it followed neither from a congruence model of faking nor from published protocols on appropriately filt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…Studies using item response theory (IRT) models (O'Brien & LaHuis, 2011;Robie, Zickar, & Schmit, 2001;Scherbaum, Sabet, Kern, & Agnello, 2013;Zickar et al, 2004) and/or structural equation modeling (SEM) techniques (Honkaniemi, Tolvanen, & Feldt, 2011 2012; Ziegler & Buehner, 2009;Ziegler et al, 2015) have found that faking behavior differs between tests, items and individuals, and is hard to disentangle. Additionally, examining response latencies has provided insights into response processes (Holden, Kroner, Fekken, & Popham, 1992;Holden & Lambert, 2015;Komar, Komar, Robie, & Taggar, 2010). The most used method of detecting faking in practical as well as research settings is using SDR scales (Goffin & Christiansen, 2003;O'Connell, Kung, & Tristan, 2011).…”
Section: How Can Faking Be Detected? In Quest Of a Faking Fingerprintmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies using item response theory (IRT) models (O'Brien & LaHuis, 2011;Robie, Zickar, & Schmit, 2001;Scherbaum, Sabet, Kern, & Agnello, 2013;Zickar et al, 2004) and/or structural equation modeling (SEM) techniques (Honkaniemi, Tolvanen, & Feldt, 2011 2012; Ziegler & Buehner, 2009;Ziegler et al, 2015) have found that faking behavior differs between tests, items and individuals, and is hard to disentangle. Additionally, examining response latencies has provided insights into response processes (Holden, Kroner, Fekken, & Popham, 1992;Holden & Lambert, 2015;Komar, Komar, Robie, & Taggar, 2010). The most used method of detecting faking in practical as well as research settings is using SDR scales (Goffin & Christiansen, 2003;O'Connell, Kung, & Tristan, 2011).…”
Section: How Can Faking Be Detected? In Quest Of a Faking Fingerprintmentioning
confidence: 99%
“…The trouble of detecting faking on an individual level can be illustrated with the response latencies approach (Holden & Lambert, 2015;Komar et al, 2010). Holden and colleagues (1992) proposed a congruence model of faking.…”
Section: Insights Into Response Process In Fakingmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the faking research is cross-sectional, and participants receive instructions either to answer honestly ("honest conditions") or to make a good impression or to make a specific impression of themselves ("faking conditions") (Shoss and Strube 2011;Tett et al 2012;Topping and O'Gorman 1997). In the endeavour to identify and avoid the faking behaviour when answering to personality tests, some strategies were devised such as the use of social desirability scales or the use of response times (Donovan et al 2003;Holden and Lambert 2015). However, how faking may affect personality assessment usefulness in the medical selection field has been poorly addressed.…”
Section: Introductionmentioning
confidence: 99%